2002
DOI: 10.1177/002204260203200410
|View full text |Cite
|
Sign up to set email alerts
|

A Drug Court Outcome Evaluation Comparing Arrests in a Two Year Follow-Up Period

Abstract: Since the first drug court in Miami in 1989, the drug court movement has spread throughout the United States, influencing how drug-involved offenders are treated in the criminal justice system. This paper reports on an outcome evaluation of a drug court in San Mateo County, California. Arrest rates were compared for drug court participants (N=618) and non-participants (N=75), and for graduates (N=257) and non-graduates (N=361). Factors associated with rearrest were assessed for participants in both groups. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 6 publications
4
73
1
Order By: Relevance
“…Hickert, Boyle, and Tollefson (2009) studied graduates and terminated clients in a Salt Lake City, Utah, drug court and found two factors affected the likelihood of completion, spending time with family rather than with friends or alone and older age. Wolfe et al (2002) found that graduates compared to nongraduates were more likely to have had a prior drug felony, spent significantly less time in pretrial custody, received more sanctions, and were more likely to be employed when released from the program. Recent work by developed and tested a logistic model to predict drug court graduation in a metropolitan Texas court.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…Hickert, Boyle, and Tollefson (2009) studied graduates and terminated clients in a Salt Lake City, Utah, drug court and found two factors affected the likelihood of completion, spending time with family rather than with friends or alone and older age. Wolfe et al (2002) found that graduates compared to nongraduates were more likely to have had a prior drug felony, spent significantly less time in pretrial custody, received more sanctions, and were more likely to be employed when released from the program. Recent work by developed and tested a logistic model to predict drug court graduation in a metropolitan Texas court.…”
Section: Literature Reviewmentioning
confidence: 94%
“…It is difficult to compare recidivism rates across studies because different outcomes are used, different time frames are studied, and different comparison groups are selected, as Wolfe, Guydish, and Termondt (2002) point out. Much of the research, however, has indicated promising effects of drug court participation on recidivism rates compared to probation (for no difference between drug court participants and controls, see Bavon, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These decisions produced a single odds ratio based on a dichotomous measure for all offenses for 49 of the 55 drug court-comparison contrasts. For the remaining six (Roehl 1998;Dickie 2000;Craddock 2002;Listwan et al 2003;Wolfe et al 2002;Rodriquez and Webb 2004), an average odds ratio was computed across the separate indicators of recidivism. For non-drug offenses, an average odds ratio was computed for seven of the 55 drug courtcomparison contrasts (Gottfredson et al 1996;Johnson et al 1998;Johnson and Latessa 2000;Roehl 1998;Cosden et al 1999;Listwan et al 2001a, b), and, for drug offenses, an average odds ratio was computed for two of the 55 drug courtcomparison contrasts (Roehl 1998; Rodriquez and Webb 2004).…”
Section: Effect Size Analysismentioning
confidence: 99%
“…Although not all drug court evaluations report reductions in recidivism for drug court participants (Meithe et al, 2000;Wolfe et al, 2002), a summary of drug court evaluation studies conducted between 1999 and April 2001 (Belenko, 2001) identified several studies reporting significantly lower recidivism rates among drug court participants than comparison offenders (Brewster, 2001;Deschenes et al, 2001;Truitt et al, 2000;Gottfredson & Exum, 2002). In addition, the United States Government Accountability Office (GAO) report on the efficacy of drug courts (GAO, 2005), most of the adult drug court programs evaluated demonstrated reductions in recidivism, at least during the program participation period (i.e., 12 months postbaseline).…”
Section: Previous Researchmentioning
confidence: 99%